Comparison of De Vaga Versus Ring Annuloplasty in Patients with Moderate to Severe Tricuspid Regurgitation - Javed Iqbal, Faridullah Khan, Naveeda Javed, Javed Iqbal, Faridullah Khan, Naveeda Javed (Journal of Rawalpindi Medical College, 2019)
Background: To compare outcome of Tricuspid Regurgitation (TR) between De Vaga technique and ring annuplasty in term of achieving adequate pulmonary artery pressure (PAP) and functional outcome. Methods: In this comparative study adult patients(n=100) who underwent Mitral valve surgery with Tricuspid repair were enrolled and divided into two groups .Group A underwent MVR and TR repair using DEVAGA Technique (n=50) and group B had MVR with Tricuspid Repair Ring Annuloplasty (n=50). In the De Vega annuloplasty technique, 2 pledgeted parallel running 4-0 polypropylene stitches are placed at 3-4-mm intervals in a semicircular manner from the postero-septal to the antero-lateral commissure and tied. A valve gauge appropriate to the body surface area was used to determine the amount of anterior and posterior annular constriction. Results: Females were predominant in this study. The duration of surgery was found out to be 66.4 minutes in group A compared to 71.0 minutes in group B(statistically not significant). Stay in the ICU and overall hospital stay was also found similar in both groups (p-value, 0.68). There was no statistically significant difference in postoperative functional capacity distribution (PAP) according to the surgical technique (p-value, 0.19). Conclusion: Devaga repair is as durable as prosthetic ring annuloplasty with added benefits of simple, cost effective and time saving technique.